Methane Oxidation to Methanol Catalyzed by Cu-Oxo Clusters Stabilized in NU-1000 Metal–Organic Framework - Ikuno, Takaaki; Zheng, Jian; Vjunov, Aleksei; Sanchez-Sanchez, Maricruz; Ortuño, Manuel A; Pahls, Dale R; Fulton, John L; Camaioni, Donald M; Li, Zhanyong; Ray, Debmalya; Mehdi, B. Layla; Browning, Nigel D; et al. (Journal of the American Chemical Society, 2017)
Copper oxide clusters synthesized via atomic layer deposition on the nodes of the metal–organic framework (MOF) NU-1000 are active for oxidation of methane to methanol under mild reaction conditions. Analysis of chemical reactivity, in situ X-ray absorption spectroscopy, and density functional theory calculations are used to determine structure/activity relations in the Cu-NU-1000 catalytic system. The Cu-loaded MOF contained Cu-oxo clusters of a few Cu atoms. The Cu was present under ambient conditions as a mixture of ∼15% Cu+ and ∼85% Cu2+. The oxidation of methane on Cu-NU-1000 was accompanied by the reduction of 9% of the Cu in the catalyst from Cu2+ to Cu+. The products, methanol, dimethyl ether, and CO2, were desorbed with the passage of 10% water/He at 135 °C, giving a carbon selectivity for methane to methanol of 45–60%. Cu oxo clusters stabilized in NU-1000 provide an active, first generation MOF-based, selective methane oxidation catalyst.